Correlation study between the characteristics of the test items and the types of student errors in advanced calculus - Yuliyani, Rahmawati; Tama, Bayu Jaya; Rezeki, Sri (Cendikia : Media Jurnal Ilmiah Pendidikan, 2025)
Students often repeat the same mistakes from year to year, these mistakes can come from various factors, both internal and external. Here we try to look at the external factors, one of which is the question item, whether the question is really too difficult or has low differentiation power, resulting in difficulties for students in answering it. On the other hand, we also want to know what types of errors students often experience so that we can minimize the repetition of these errors in the future. This research was conducted to see from both sides whether there was a match or not. The types of errors that are often made by students in advanced calculus courses are conceptual errors, procedural errors and operational errors. The sampling method was carried out twice, one for the sample of student error types and one for the sample of question item analysis. Here we want to know whether there is a relationship between the characteristics of the questions in the form of level of difficulty and the different strengths of the questions and the types of errors made by students in writing advanced calculus questions. From the results of the analysis of both, the results obtained were in accordance with the results, namely that although the questions tend to be moderate and relatively easy, students have not been able to maximize their learning outcomes in advanced calculus courses due to their lack of understanding at the basic level which can be seen from the types of errors such as errors in multiplication operations, errors in calculating integrals and not writing down formulas or concepts that apply in the questions. It is hoped that teachers can add small notes as a connecting thread that is broken in the concept of student understanding.